HUBUNGAN FAKTOR RISIKO TERHADAP KEPATUHAN PENGOBATAN DIABETES MELLITUS DI PUSKESMAS CIKAMPEK - Larasati Fauziah Yakub; Mikha Ayu Lia Ningsih; Nirwana Aulia Putri; Maya Arfania (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
According to the International Diabetes Federation (IDF) the prevalence of DM was 366 million in 2011, and it's predicted that in 2030 it'll increase to 552 million. In 2020 as many as 1 million people in West Java suffer from DM. With 139 thousand people of whom are residents in Karawang Regency. According to WHO in 2003 only about 50% adherence rate of chronic disease treatment in developed countries. Factors that cause low levels of adherence include running out of medication, forgetting to take medication, knowledge, motivation for treatment, and family support. In addition, age, nutritional status, education level, occupation, and income can also affect medication adherence in DM patients. The purpose of this study was to determine adherence to DM treatment at the Cikampek Health Center and how the relationship between risk factors for adherence to DM treatment. This research is an analytic observational study with a cross-sectional design. The population and sample of this study were all DM patients who underwent treatment methods at the Cikampek Health Center, using total sampling. This research was conducted at the Cikampek Health Center, using MMAS-8 questionnaire and then the data were analyzed using the chi-square test. The results of the study showed that 104 respondents had low adherence to treatment at the Cikampek Health Center, 42.3% had low adherence, and there was no correlation between risk factors and DM treatment adherence. Keywords: Adherence, Diabetes Mellitus, Risk Factor